SUPERVISION OVER CONVICTS AFTER SERVING A PRISON SENTENCE - Milić, Ivan; Drakić , Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Convicts who have committed crimes, which the Act on Special Measures for Preventing the Commission of Sex Crimes against Minors applies to, are subject to special measures after serving their prison sentence. The special measures are applied by force of law and must be enforced for at least two and at longest for twenty years after the prison sentence has been served. The author focuses on these special measures.